DAMPAK SUPERVISI BIMBINGAN DAN KONSELING TERHADAP KINERJA GURU BK : Studi Kasus di SMA Kabupaten Majalengka - Eka Rahmawati, - (2020)
Supervision is a part of the guidance and counseling accountability that aims to improve the professional and personal competence of guidance and counseling teachers. The research aims to explore the phenomenon of guidance and counseling supervision in senior high school units and their impact on guidance and counseling teacher performance. The study used qualitative research with a case study design, involving seven participants of guidance and counseling teachers and one participant is guidance and counseling supervisor in Senior High School Majalengka Regency. The research instrument used interview guidelines and documentation studies. The result of the research is supervision has a positive impact on guidance and counseling teacher performance, that shown in improving the performance on personality and professional competencies. Supervision is carried out in six aspects: (1) the supervision function is dominated by the administration and evaluation functions; (2) the aim is to increase professionalism and performance; (3) the target subject is all of guidance and counseling teacher in High School and the change target is improve performance; (4) supervision activities not refer to counselor supervisors guidelines and are dominated by administrative supervision; (e) personal relationships are only formal relation without differences, attachment and suitability has impact to guidance and counseling teacher's feelings; (f) evaluation is less structured and carried out without any guidelines to be evaluated. Implications of research for guidance and counseling supervisors are to take the research findings by designing plans for development and improve activities of supervision implementation. Keywords: supervision, performance, guidance and counseling